2023
DOI: 10.1007/s42113-023-00190-5
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Environmental Statistics and Predictive Gaze Behaviour During a Manual Interception Task: Eye Movements as Active Inference

David Harris,
Sam Vine,
Mark Wilson
et al.

Abstract: Human observers are known to frequently act like Bayes-optimal decision-makers. Growing evidence indicates that the deployment of the visual system may similarly be driven by probabilistic mental models of the environment. We tested whether eye movements during a dynamic interception task were indeed optimised according to Bayesian inference principles. Forty-one participants intercepted oncoming balls in a virtual reality racquetball task across five counterbalanced conditions in which the relative probabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…Eye tracking data was lost for one participant in one condition due to a recording error. In a previous study, we observed effects in the range of R 2 = .03-.06 for changes in predictive gaze position in this task (44). Power curves using the simr package for R (45) showed that for linear mixed effects models (with participant as a random factor), 36 trials for 30 participants was sufficient to detect effects at the lower end of this range with more than 85% power (see power curves in the supplementary files: https://osf.io/2amdv/).…”
Section: Participantsmentioning
confidence: 62%
See 3 more Smart Citations
“…Eye tracking data was lost for one participant in one condition due to a recording error. In a previous study, we observed effects in the range of R 2 = .03-.06 for changes in predictive gaze position in this task (44). Power curves using the simr package for R (45) showed that for linear mixed effects models (with participant as a random factor), 36 trials for 30 participants was sufficient to detect effects at the lower end of this range with more than 85% power (see power curves in the supplementary files: https://osf.io/2amdv/).…”
Section: Participantsmentioning
confidence: 62%
“…The virtual environment, which had the visual appearance of an indoor racquetball court, was developed using the gaming engine Unity (v2019.3.1f; Unity Technologies, San Francisco, CA) (see Fig 1). The same task has been used to study predictive eye movements in previous papers (44,46). The task was displayed using an HTC Vive head-mounted display (HTC Inc., Taoyuan City, Taiwan).…”
Section: Task and Materialsmentioning
confidence: 99%
See 2 more Smart Citations